Understanding meaning in online advertisements through pragmatic analysis of jargons (slangs) and types of pragmatic meaning in advertising texts - Qurbonova , Dilnoza (The Lingua Spectrum, 2025)
This article explores the use of jargon (slang) words in online advertisements, focusing on the types of pragmatic meanings conveyed in advertising texts and identifying which of these meanings is most dominant. The main objective of the study is to examine how jargon words are expressed in online advertisements and to analyze their pragmatic functions. In particular, the phenomenon of slang in online advertising is emerging as a stylistic trend or mode of speech within society. Jargon has become an integral part of everyday communication, frequently appearing in daily conversations. Advertisers intentionally use slang in online advertisements to capture the attention of the younger generation and engage them more effectively. This research employs multiple methods. As research material, all the sentences found in 12 selected online advertisements were analyzed in detail.